Acceleration of the identification of sepsis‐inducing bacteria in cultures of dog and cat blood. (16th July 2019) - Ulrich, S.; Gottschalk, C.; Straubinger, R. K.; Schwaiger, K.; Dörfelt, R.
Abstract : Objectives: To evaluate matrix‐assisted laser desorption ionisation time of flight mass spectrometry (MALDI‐TOF MS) combined with the Sepsityper kit (Bruker Daltoniks GmbH, Bremen) for the direct detection of bacterial species from inoculated blood cultures from dogs and cats. Materials and Methods: Canine and feline blood samples were inoculated with typical sepsis‐causing bacteria such as Staphylococcus intermedius, Staphylococcus aureus, Streptococcus canis, Enterococcus faecalis, Escherichia coli and Pseudomonas aeruginosa at two distinct concentrations (each in triplicate), resulting in 72 blood culture bottles incubated at 37°C. Samples were comparatively analysed with MALDI‐TOF MS after preparation with the Sepsityper kit and also by standard bacteriology (culturing and biochemical characterisation). Results: Bacterial species identified from agar plates and by MALDI‐TOF MS from blood culture bottles were identical for all samples. The MALDI Biotyper software (Bruker Daltoniks) correctly identified all bacterial strains from inoculated canine and feline blood with analysis indicating very good precision. Clinical Significance: MALDI‐TOF MS analysis combined with the Sepsityper kit is a reliable tool for a quick detection of veterinary‐relevant bacterial species directly from blood culture bottles. This approach could reduce the time for identification of critical species to only 24 hours.